VARIABEL MAKROEKONOMI YANG MEMPENGARUHI INDEKS HARGA SAHAM INDONESIA, THAILAND, MALAYSIA, DAN VIETNAM - Tjandrasa, Benny Budiawan; Aribowo, Agus; Jewarut, Rofinus (Jurnal Keuangan dan Bisnis, 2021)
One of the indicators of a country's economic growth is the stock price index in the country. The purpose of this study is to determine what factors are most influential and how significant the influences on the stock price indexes in Indonesia, Malaysia, Thailand, and Vietnam. The data panel was formed based on secondary data from January 2012 to December 2019 in Indonesia, Thailand, Malaysia, and Vietnam with 384 samples. The dependent variable of this study is the stock market index, while the independent variables are the foreign exchange rate, volatility index, and government bond yield. The equation for the direction test in this study used a multivariate regression model. The results show that the foreign exchange rate, volatility index, and government bond yield together have a significant effect on the stock market index. Partially, the foreign exchange rate has a positive and significant effect on the stock market index, while the volatility index and the government bond yield have a negative and significant effect on the stock market index.